Evaluating growth references used in Switzerland: a comparative analysis in Zurich schoolchildren (Swiss Medical Weekly, 2025)
INTRODUCTION: The Swiss Society of Paediatrics currently recommends the growth references of the World Health Organization (WHO), while the Paediatric Endocrinology Centre Zurich (PEZZ) has proposed alternative growth references. Specialists and researchers also use International Obesity Task Force (IOTF) references to define overweight and obesity. We investigated the fit of anthropometric measurements from schoolchildren in the canton of Zurich to these three growth references and assessed the prevalence of overweight, obesity and short stature across the three references.METHODS: We analysed data from 3755 children aged 6–17 years in the cross-sectional LuftiBus in the School (LUIS) study, collected in the period 2013–2016 in the canton of Zurich. We calculated z-scores of height, weight and body mass index (BMI) based on WHO, PEZZ and IOTF references. We compared the mean and distribution of z-scores to the expected standard normal distribution using the Anderson-Darling test. We classified overweight, obesity and severe obesity based on cutoff values given by the three references. We defined short stature as